Suicide: Managing self-directed violence? - Gupta, Deepak; Kumar, Sarwan (Indian Journal of Community Health, 2018)
The Centers for Disease Control and Prevention have put forth recommendations to document events in terms of well-defined categories of self-directed violence even though the evolution of terminology for decriminalization and de-stigmatization from “self-murder” to “suicide” to “self-directed violence” may be just avoiding calling a spade a spade. Suicide causes mortality (and morbidity if suicide attempt) in an individual leading to (a) physical suffering to others by injuring them during-and-after the act, (b) psychological toll on the next-of-kin, and (c) isolation of society due to its suicide-statistics and economic losses with overall loss of spirit to pursue happiness potentially resulting more mortality if morbidity becomes too severe for the affected. What is the story (myth) instigating an individual to commit (or think of committing) the act of self-directed violence? And what is the story (myth) in the society that is allowing the act in some instances while prohibiting and sometimes even punishing the act in other instances? We believe that Switzerland can provide an apt example to understand suicide. Swiss ideology may inspire societies around the world to recognize their stories (myths) when they scientifically decipher prevalence of self-directed violence “suicide” even in nonhuman animals. Consequently, astounding statistics of physician suicide call for action from physicians’ community to understand peers when none can remain untouched by harsh reality of unique stress which physicians’ workspace entails. One of the possible remedies may be thoughtlessness (a form of meditation) which may require strenuous practicing; however, the first step towards achieving it may possibly involve mindfulness (another form of meditation) inspiring peers to learn the need to refocus onto whatever good there is over whatever better there could have been. Essentially, the conception of birth and the birth itself is always planned to be joyful; and the embrace of death itself and the life after death is always purported to be peaceful.